2001
DOI: 10.1086/322164
|View full text |Cite
|
Sign up to set email alerts
|

Milking Strategy in Subantarctic Fur SealsArctocephalus tropicalisBreeding on Amsterdam Island: Evidence from Changes in Milk Composition

Abstract: Milk composition was investigated throughout the 10-mo pup-rearing period in subantarctic fur seals (Arctocephalus tropicalis) breeding on Amsterdam Island. The mean milk composition was 42.8% +/- 5.7% lipid, 12.1% +/- 1.5% protein, and 42.6% +/- 7.3% water. Subantarctic fur seals breeding on Amsterdam Island produced one of the richest milks ever reported in otariids (20.4 +/- 2.9 kJ/g), with lipid content contributing 85% of total gross energy. The high lipid levels measured in the milk of subantarctic fur s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…The autumn peak in milk gross energy (Georges et al 2001) may compensate for longer trips undertaken by the females during that period. However, although pups are adapted to long-term fasting periods , the concurrent decreasing energy content of the milk (Georges et al 2001) and increasing requirements of pregnancy (Oftedal 1985) are likely to reduce a female's capacity to fulfill the requirements of its pup during winter. Furthermore, the greater mean seasonal trip duration (see Fig.…”
Section: Maternal Performance and Pup Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The autumn peak in milk gross energy (Georges et al 2001) may compensate for longer trips undertaken by the females during that period. However, although pups are adapted to long-term fasting periods , the concurrent decreasing energy content of the milk (Georges et al 2001) and increasing requirements of pregnancy (Oftedal 1985) are likely to reduce a female's capacity to fulfill the requirements of its pup during winter. Furthermore, the greater mean seasonal trip duration (see Fig.…”
Section: Maternal Performance and Pup Growthmentioning
confidence: 99%
“…In this context, body length represents an important component of the body's reserve strategy, especially since foraging zones are located far away from the rookery. Female subantarctic fur seals breeding on Amsterdam Island have the largest body size of this species (Bester & Van Jaarsveld 1994, Robinson et al 2002, and the milk they produce is among the richest of all otariids (Georges et al 2001). This suggests a phocid-like strategy (Trillmich 1996); that is, they may rely more on their fat reserves than any other otariid species.…”
Section: Maternal Performance and Pup Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldsworthy and Crowley (1999) suggested that the difference in growth rates could reflect either a higher milk consumption rate in Antarctic fur seals or greater metabolic expenditure by subantarctic fur seals. However, the limited information on pup metabolic rates for the species is restricted to their allopatric sites (making comparisons difficult) and there is no information on their milk consumption rates at sympatric sites (Arnould et al, 1996a(Arnould et al, , 2001Beauplet et al, 2003;Georges et al, 2001;Guinet et al, 1999). Furthermore, while mass gain differs between the species, it is not known whether the divergent lactation strategies influence the composition of growth and development (Owens et al, 1993;Spray and Widdowson, 1950).…”
Section: Introductionmentioning
confidence: 99%
“…Bathymetry was used to determine when a seal left continental shelf waters. Bathymetry values were calculated for each seal at 15 min intervals along each interpolated satellite track and were obtained from the General Bathymetric Chart of the Oceans (GEBCO) 1 × 1 km World Bathymetry Grid (2.1).Milk FA can originate from recent dietary intake and/or from mobilization of stored body fat, depending on when the seal last fed (Georges et al 2001, Staniland & Pond 2005, Budge et al 2006 fore reflect a combination of the most recent dietary intake and a longer dietary history. To ensure the foraging trip used to classify foraging location (i.e.…”
mentioning
confidence: 99%